ANALISIS PENTINGNYA PUBLICH SPEAKING DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI INDONESIA ERA SOCIETY 5.0 - Melysa Dara Agustin; Sri Mulyani Rusli (Jurnal Pendidikan Nusantara, 2025)
This study is motivated by the growing importance of public speaking in improving the quality of education in Indonesia, particularly in the era of Society 5.0. The development of Society 5.0 requires the education sector to possess more adaptive communication skills that align with technological advancements and the demands of 21st-century competencies. In this context, public speaking becomes a crucial skill that needs to be strengthened to ensure learning processes are more effective and relevant. This research aims to examine the urgency of public speaking skills in enhancing the quality of education in Indonesia during the Society 5.0 era. The study employs a descriptive-analytical approach by reviewing various literature related to public speaking, modern competencies, and educational transformation. The findings indicate that public speaking skills help clarify communication between teachers and students, enhance students’ self-confidence, and support collaborative and project-based learning. Moreover, this skill contributes to the integration of technology in education, such as digital presentations, educational videos, and virtual discussions. The study also finds that strengthening public speaking fosters an active and communicative learning environment, which positively impacts learning outcomes. Overall, public speaking is identified as an essential competency that must be systematically integrated into educational practices to support the development of high-quality and competitive education in the Society 5.0 era.